Effect of Silicon State on Microstructure and Properties of Al-1%Si Alloy During Severe Plastic Deformation - TANG Jingzhao (Editorial Office of Journal of Shanghai Jiao Tong University, 2021)
Alloy elements can influence the microstructure evolution of aluminum alloys in the state of solid solute atoms or nano-precipitated silicon particles, but it is still a controversial subject which form has a more significant effect on the microstructure of aluminum alloys. Therefore, taking the Al-1%Si alloy as the research object, the ratio of precipitation state and the solid solution state of the silicon atoms was changed before deformation and a multi-pass accumulative roll-bonding method was used to achieve large deformation. In order to compare the influence of solid solute atoms and nano-precipitated silicon particles on the structure and properties of aluminum alloy during deformation, a comparative study was conducted on the evolution of nano-precipitated silicon particles, grain size, and dislocation density in the process of reaching the saturation state of the microstructure and mechanical properties. The results show that the initial samples with less nano-precipitated silicon particles and more solute silicon atoms have a higher saturated dislocation density and a smaller saturated grain size after deformation, corresponding to a higher saturated yield strength. Solid solute silicon atoms dispersed in the Al-1%Si alloy have a better overall effect than nano-precipitated silicon particles of the same volume in preventing the dynamic recovery of dislocations, which is consistent with the theoretical analysis of dislocations. The dislocation recovery ability in the material affects its saturated grain size. The stronger the dislocation recovery capacity, the larger the saturated grain size.